Contrasting trait assembly patterns in plant and bird communities along environmental and human‐induced land‐use gradients. Issue 6 (14th June 2016) - Concepción, Elena D.; Götzenberger, Lars; Nobis, Michael P.; de Bello, Francesco; Obrist, Martin K.; Moretti, Marco
Abstract : Human‐driven environmental changes can induce marked shifts in the functional structure of biological communities with possible repercussion on important ecosystem functions and services. At the same time it remains unclear to which extent these changes may differently affect various types of organisms. We investigated species richness and community functional structure of species assemblages at the landscape scale (1 km 2 plots) for two contrasting model taxa, i.e. plants (producers and sessile organisms) and birds (consumers and mobile organisms), along topography, climate, landscape heterogeneity, and land‐use (agriculture and urbanization) gradients in a densely populated region of Switzerland. Our study revealed that agricultural and urban land uses drove marked shifts in the functional structure of biological communities compared to changes along climate and topography gradients, especially for plants, while for birds these changes were comparable. Agricultural and urban land uses enhanced divergence in traits related to resource use for birds (diet and nesting), growth forms, dispersal, and reproductive traits for plants, while it induced convergence in vegetative plant traits (plant height and leaf dry matter content). These results suggest that contrasting assembly patterns may arise within and across taxonomic groups along the same environmental gradients as result of distinct underlying processes and 'organism‐specific' environmental perceptions. Our results further suggest a potential homogenization of biological communities, as well as low functional diversity and redundancy levels of bird assemblages in our human‐dominated study region. This might potentially compromise the maintenance of key ecological processes under future environmental changes.